MENINGKATKAN KEMAMPUAN PERKALIAN MELALUI PERMAINAN POS IT KELAS II DI SDN 057224 PALUH GUSTA - Nuraida Nuraida (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
Through the use of tangible objects, this study seeks to improve the understanding of multiplication. To conduct this form of experimental study, records were taken at SDN 057224 Paluh Gusta to ascertain the students' ability to talk about multiplication. only. method for collecting data involving monitoring. The findings show that many students still do not take multiplication seriously. To support students' success in thinking critically about multiplication, tangible things are sought as a consequence of achieving students can think critically about multiplication while learning. It is easier to carry out learning tasks in the classroom when there are tangible objects that can be used as media to calculate multiplication by teachers or students.